Resiliensi Organisasi dan Keunggulan Bersaing Berkelanjutan: Mediasi Manajemen Krisis di Pendidikan Tinggi - Widiantoro, Didik (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
This study examines the influence of Organizational Resilience on Sustained Competitive Advantage, with Crisis Management as a mediating variable in the context of private universities in Indonesia. Employing a quantitative approach, data were analyzed using path analysis to test the relationships between variables. The findings indicate that Organizational Resilience has a direct effect on Sustained Competitive Advantage (β = 0.0897, Z = 1.94, p = 0.052), though the effect is marginally significant. Organizational Resilience also significantly influences Crisis Management (β = 0.5402, Z = 14.17, p < 0.001), and Crisis Management significantly affects Sustained Competitive Advantage (β = 0.3489, Z = 6.81, p < 0.001). The mediating effect of Crisis Management is significant (Indirect Effect = 0.1885, Z = 6.14, p < 0.001; Total Effect = 0.2781, Z = 7.07, p < 0.001), indicating partial mediation. These results suggest that Organizational Resilience supports Sustained Competitive Advantage both directly and indirectly through effective Crisis Management. This study contributes theoretically to understanding the dynamics of organizational resilience in the Indonesian higher education sector and offers practical recommendations for private universities to enhance competitiveness through systematic crisis management strategies amid global disruptions and competition with state universities.